Growth Comparison of Red Jabon in North Bolaang Mongondow and North Minahasa - irawan, Arif Irawan; Hidayah, Hanif Nurul Hidayah (Forestry Department, University of Muhammadiyah Makassar, 2016)
Red Jabon is priority species that projected to be developed in plantation forests of North Minahasa Regency. Red Jabon is can adapt well various environmental conditions. The natural habitat of the red Jabon in North Sulawesi region was known in North Bolaang Mongondow. This study aimed to compare the growth of red jabon at the age of 1 year in North Minahasa Regency and North Bolaang Mongondow. The experiment was conducted in two (2) locations i.e. in Talawaan Village (North Minahasa Regency) and Nunuka Village (North Bolaang Mongondow). Two independent samples t test was conducted to determine the differences in height and diameter growth parameters at two test sites.The results showed that there was no difference in the growth of red Jabon between North Minahasa and North Bolaang Mongondow. The average height and diameter of red Jabon in North Minahasa Regency is at 215.84 cm and 4.34 cm, while the same parameters of North Bolaang Mongondow amounted to 231.79 cm and 4.14 cm. The development efforts on the plantations of red Jabon North Minahasa Regency need to be improved because of the environmental conditions in this region is very suitable for the growth of red Jabon.